Continuous Approach in the Theory of Interaction of Charged Particles with Solids - N. T. Kvasov; V. I. Yarmolik; E. R. Pavlovskaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
In this paper, the main radiative processes, for the first time, are considered within the framework of continuum physics, where the motion of charged particles occurs in a continuous resisting medium.Within the analysis, new characteristics of the interaction of ions with matter are introduced. The proposed formalism also uses some results of modern corpuscular theory. It allows giving a physically clear space-time description of the processes and phenomena analyzed in this paper. Further in this paper, the authors have estimated, with a high degree of accuracy, the ranges of ions in various materials; constructed their energy loss profiles; determined the mean free path and mean free time of the charged particles in matter, and proposed the formalism for analyzing the radiative change in the physical properties of solids. For the first time, the physical nature of the main characteristic of the radiation resistance of materials, i.e., the threshold displacement energy, has been studied in detail, and the formula for its calculation has been derived by the authors.